Prevalence of Progression Toward Renal Calculi in Patients Suffering from Urinary Tract Infection: A Cross-Sectional Study - Syed Waseem Ahmed Gilani, Aatif Hassan Shaikh, Abdul Jabbar Pirzada, Irfan Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the frequency of renal stones in the patient suffering from urinary tract infection (UTI) Study design: A cross-sectional study Place and Duration: This study was conducted at Northwest General Hospital Peshawar from June 2021 to June 2022 Methodology: A total of 115 patients with the symptoms of recurrent urinary tract infection were included in the study. Those patients who had a positive history of upper and lower urinary tract stones, renal tumors, already present renal calculi, and patients with renal failure, were not added to the present study. A specially designed proforma was filled out by all the patients so that the required data could be acquired and analyzed. Results: The mean age of the patients was 36.1±15.2 years ranging from 15 years to 60 years. Urinary tract infection was confirmed in 92 (80%) patients. The most prevalent organism detected on urine culture was E.Coli (29%). Some of the other organisms majorly detected were Proteus (18%), Pseudomonas (8%), Klebsiella (10%), and Staphylococcus aureus (4%). The renal stone disease was found in 18 (19.56%) patients out of which 12 (13.04%) were male and 6 (6.52%) were female. The mean age of the patients presented with renal stones was 32.65±15.3 years. The male-to-female ratio of the patients with renal stones was 1.5:1. Conclusion: A large number of patients with urinary tract infections can develop the renal stone disease. Certain microorganisms are significant in this progression and resulting in renal stones. Keywords:Urinary tract infection, renal stone disease, Microorganisms, E.Coli